A territorialização libanesa em Guarapuava PR - Muzzolon, Anderson (2012)
The analysis of socio-spatial relations over time, formed by the process of territorialization of cultural groups in the city, is one way to understand the dynamics of production of portions of the urban space. This is the approach that we develop in relation to the Lebanese and their descendants living in Guarapuava, the purpose of seeking to rebuild his trajectory in the city and its contribution to the consolidation of two major shopping streets of the city: the streets Guaíra and Saldanha Marinho. The research had as main sources of various documents, both the city hall, museum and public library, and the Lebanese themselves, and especially the memory of several generations of this cultural group, which we seek access through interviews. Thus, the study sought to fill a gap in studies on Guarapuava, by considering a group neglected to date, the historiography and geography.